Waterborne epoxy coating compositions with self-emulsifying amine hardeners - Kowalczyk, K.; Spychaj, T. (Polimery, 2022)
Three waterborne varnish compositions and epoxy coatings prepared of liquid bisphenol A - based epoxy resin "Epidian 6" and self-emulsifying hardeners (amine adduct type) were investigated. The effects of hydrophilicity of the hardeners used on the technological properties (fluidity, pot life, drying time - Table 1) and useful ones (adhesion, scratch resistance and water uptake - Table 2) of the coatings on the steel substrate, after curing at room temperature, were determined.